â€œKESULITAN PADA ASPEK-ASPEK WRITING MAHASISWA DENGAN ENGLISH PROFICIENCY LEVELS YANG BERBEDAâ€ - Wigati, Fikri Asih (Majalah Ilmiah SOLUSI, 2015)
The Indonesian studentsâ€™ writings are still not satisfying. Particularly in a class comprising many proficiency levels, students often find problems in essay writing. This study addresses the question of the problems faced by students at the English language proficiency of basic and upperintermediate levels in writing a descriptive essay. Participating in this study were six students who enrolled in writing IV class in the fourth semester of English Education Program in a university in Karawang. Taking the form of six descriptive essays written by the respondents, the data were collected by way of various techniques i.e. analysis of the products, observation of the writing process, and followed up by the interview with the writers. The data were later codified and juxtaposed in order to reveal various problems including technical problems in writing (content, organization, vocabulary, grammar, and mechanics). The findings show that the respondents who are at the basic level of language proficiency were faced mainly with the lack of vocabulary and the lack of capability in operating the English grammar. The upper-intermediate students tend to had different problems including composing unclear introductory paragraph, problematic complex sentences, and making grammatical mistakes. The findings of the present study offer some recommendations for the next researchers to investigate the same field and also for teachers and students to improve the teaching learning process particularly, in writing a descriptive essay.